Action observation network in childhood: a comparative fMRI study with adults. Issue 6 (5th November 2015) - Biagi, Laura; Cioni, Giovanni; Fogassi, Leonardo; Guzzetta, Andrea; Sgandurra, Giuseppina; Tosetti, Michela
Abstract: Very little is known about the action observation network and the mirror neuron system (AON/MNS) in children and its age‐related properties compared with those observed in adults. In the present fMRI study we explored the activation of areas belonging to the AON/MNS in children and adults during observation of complex hand‐grasping actions, as compared to observation of simple grasping acts executed with the left and the right hand, seen from a first person perspective. The results indicate that during the action observation tasks in children there was activation of a cortical network similar to that found in adults, including the premotor cortex, the posterior part of the inferior frontal gyrus and the posterior parietal lobe. However, the activation in children was more widespread and showed a higher inter‐subject variability compared with adults. Furthermore, the activated network seems more lateralized to the left hemisphere in adults and more bilateral in children, with a linear growth of lateralization index as a function of age. Finally, in children the activation in the anterior intraparietal cortex (AIP) of each hemisphere was higher during observation of the contralateral hand (hand identity effect) and during the observation of complex actions relative to simple grasping acts, confirming the role of AIP for action‐related hand identity previously described in adults. These results support the assumption that structure and size of action representations are sensitive to mechanisms of development and show physiological plasticity. These properties of the AON/MNS could constitute a powerful tool for spontaneous reorganization and recovery of motor deficits after brain injury in children and in adults, as well as for specific rehabilitation programmes. Abstract : In this study, functional MRI was used to explore the activation of the action‐observation network in children and adults. Respect to adults, children show a similar pattern of fMRI activation for observation of manual action, but less lateralized and with a higher inter‐subject variability. Moreover, as in adults, the anterior intraparietal cortices (AIP) of children present a hand identity effect, showing higher response during observation of the contralateral hand (hand identity effect) and during the observation of complex actions relative to simple grasping acts.